THE RELATIONSHIP BETWEEN ETHICAL CLIMATE AND CONFLICTS MANAGEMENT STRATEGIES IN WRESTLING CLUBS - Zynalabedin Fallah,; Bahman Tayebi, (Sport Scientific And Practical Aspects, 2025)
The aim of this research was to study the relationship between ethical climate and conflicts management strategies in wrestling clubs. The research method was descriptive-correlational type and data was collected through the field manner. The statistical population consisted of all experienced wrestlers (at least four years) in wrestling clubs of Golestan Province (N= 190). The sample was randomly selected based on Morgan sample size sampling table (n= 125). Data were collected using ethical climate questionnaires of Victor and Cullen (1988) and Putnam and Wilson conflict management strategies questionnaire (1982). Descriptive and inferential statistics were used to analyze the data. Percentage and frequency were used to describe qualitative traits, while indicators of center inclination and dispersion were used for quantitative traits. Pearson correlation coefficient was used to analyze and interpret the obtained data.Results showed a significant relationship between ethical climate and conflict management strategies. In the meantime, the strongest link was found between dimensions of Caring, ethical climate, strategies for cooperation and conflict management reconciliation, as well as between independent aspects of ethical climate and conflict management strategies. Thus, suggest that coaches should emphasize on cooperation strategy to solve and manage conflicts in wrestling clubs.